Effect of Al2O3 content and milling time on the properties of silver coated Cu matrix composites fabricated by electroless plating and hot pressing. (September 2020) - Güler, Onur; Varol, Temel; Alver, Ümit; Canakci, Aykut
Graphical abstract: Highlights: Copper powders were coated with silver by using electroless coating process. Silver coated copper-Al2 O3 composites fabricated by hot pressing method. The highest hardness was measured as 125 HB for composite samplesdue to homogeneous particle distribution. The highest electrical conductivity was measured as 88 IACS for composite samples thanks to the homogeneous silver layer. Abstract: This work aims to reveal the positive effects of silver coating and milling of copper particles on the physical properties such as density, hardness and electrical conductivity of Al2 O3 reinforced copper matrix composites. Al2 O3 particles reinforced (0.5, 1, 2, 3 and 5%wt.) silver coated and uncoated copper matrix composites were fabricated using the hot-pressing method. A scanning electron microscopy (SEM) was used to investigate the morphology of powders and microstructure of the silver coating layer and composite samples. The density (δ) and hardness of compacts was determined by the Archimede's method and Brinell hardness method, respectively. Electrical conductivity of samples was measured using Sigmascope SMP10 HF electrical conductivity measurement device and reported in the International Annealed Copper Standard (IACS). The best coating homogeneity in copper-silver core-shells was observed in milled copper powders for 2 h. The density of samples decreased but the hardness of samples increased with increasing Al2 O3 content due to hard and non conductive structure of Al2 O3 ceramic particles. The highest hardness was measured as 125 HB for silver coated copper matrix composites fabricated by using 2 h of milling and 3%wt. Al2 O3 content. 95 HB was obtained for the uncoated copper matrix composites fabricated by using 3 h of milling and 3%wt. Al2 O3 content. For composite samples, the highest electrical conductivity value was measured as 88%IACS for silver coated copper matrix composites synthesized by 2 h of milling and 3%wt. Al2 O3 content.